CLINICAL AND LABORATORY CHARACTERISTICS OF THE STATE OF ORGANS AND TISSUES OF THE ORAL CAVITY IN CHILDREN IN THE TREATMENT OF CHRONIC CATARRHAL GINGIVITIS - Rikhsieva D.F; Abdullaev J.R (Scholar Express Journals, 2022)
This article highlights the basic information based on clinical and laboratory studies aimed at further improving the methods of early diagnosis and prevention and treatment of chronic catarrhal gingivitis in children. In this scientific work, in clinical conditions in children without chronic catarrhal gingivitis and in children with this disease, the composition of gingival fluid is studied using cytological and microbiological methods, the findings are statistically processed and applied in the practice of pediatric dentistry.
Keywords: Catarrhal gingivitis; periodontal tissues; cytological analysis; children with chronic catarrhal gingivitis